Comparación del adiestramiento manual para la preparación cavitaria clase II para resina compuesta según la metodología tradicional vs el uso de una metodología innovadora en los alumnos de Pre-grado de la Escuela de Odontología de la Universidad Peruana de Ciencias Aplicadas en el periodo 2013-1 - Ticona Huamaní, Lovely Carmela (2014)
Introduction: Clinical simulation is considered a teaching strategy which helps to prevent and assess risks associated with clinical activities. Throughout the years, there have been substantial changes observed in the usage of different simulation tools. Nevertheless, only a few Peruvian universities have adopted the use of new technologies. Objective: To evaluate the manual training of the student in the preparation of class II cavities in comparison to the used teaching tools, tipodont and phantom. Additionally, to evaluate the perception of the student after the use of the two proposed. Materials and methods: A quasi-experimental study was developed with 36 undergraduate students from the Universidad Peruana de Ciencias Aplicadas having no previous experience about manual training. At the beginning, they were divided in two groups. The first group was composed by 18 students of second and third cycle who developed class II cavities with tipodont. This group was denominated group M1. The second group was composed by 18 students of fourth cycle who carried out class II cavities with phantom, and was denominated M2. Both groups developed cavitary preparations in two sessions: one initial session or A, where the students had the first contact with the simulator (tipodont or phantom) and one final or B, where the students showed their performance and skills acquired with a phantom. In this way, the groups were divided in Group M1A, students with initial tipodont; Group M1B, students with final phantom; Group M2A, students with initial phantom; and Group M2B, students with final phantom. All the cavities were evaluated by just one examiner, who was a specialist in the field of restorative dentistry and who had no knowledge of the population, groups, or sample of the study. The examiner used an operating microscope to assess the quality of the gingival margin and a digital vernier to measure the cavitary conformation. Students evaluated the effectiveness and comfort of the procedure in a two-part survey (Annex 2) that was validated by Quinn (20) and Mendoza (4) . The surveys were developed only for the group “M1”, which used tipodont and changed the simulation tool to phantom for the second evaluation. At the end of the session, all participants were asked to resolve the survey, where the students resolved the survey qualifying their past experience with tipodont (M1B1) and (M1B2), with data about the students who resolved the survey qualifying their new experience with phantom. Results: According to the results of the group M1, “M1A” had its first experience in simulation with tipodont with an acceptable quality of gingival margin of 16.67% in comparison to the group M2A, which had 5.56% in its first experience in simulation with phantom. Nevertheless, for a time “B”, M1B obtained a value of 16.67% while the group M2B obtained 33.33%. For the conformation of the cavitary preparations for independent samples (p<0.05), no statistically meaningful difference was found in both groups for both times, “A” y “B”. Statistically meaningful differences were found only for the isthmus of the occlusal box in both groups and times. In respect of the effectiveness, the group M1B1 considered a level of exigency of 3.13% for the use of tipodont in comparison to the group M1B2 that valued the exigency with 26.47% for the use of phantom. Additionally, the 21.88% of the group M1B1 considered easier the effectiveness of the tipodont in comparison to the group M1B2, in which only 9% considered it was easy. For the comfort, in the question: “I seemed to be in front of a real patient”, no member of the group M1B1 answered to be strongly agree, while the 94% of the group M1B2 considered that they were strongly agree. Conclusion: The results of the study demonstrated that the use of phantom as a simulation tool allows better training for the development of class II preparations and is better valued for the students according to their perceptions.